2010
DOI: 10.1111/j.1440-0960.2009.00616.x
|View full text |Cite
|
Sign up to set email alerts
|

Facial porokeratosis: A series of six patients

Abstract: Porokeratosis is a disorder of epidermal keratinization characterized by annular plaques with an atrophic centre and hyperkeratotic edges, and includes a heterogeneous group of disorders that are mostly inherited in an autosomal dominant fashion. Facial porokeratosis is rare and is not well documented. We present six cases of facial porokeratosis seen over a period of 15 years in a hospital in Lima, Peru. In most of the cases, porokeratosis was found in younger women without any significant past medical histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 11 publications
1
29
0
2
Order By: Relevance
“…Interestingly, this case had gross similarity to the single largest published series (12 female and 3 male patients) [1] and the subsequent individual case reports of nasal PK [5,[7][8][9].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Interestingly, this case had gross similarity to the single largest published series (12 female and 3 male patients) [1] and the subsequent individual case reports of nasal PK [5,[7][8][9].…”
Section: Discussionsupporting
confidence: 70%
“…Common sites of predilection are trunk and extremities although sporadic cases of involvement of palms and soles, face, oral mucosa, lips have been reported [5]. The present study highlights the high incidence of nasal PK among the reported cases in the world literature which is clinically and epidemiologically distinct from other types of PK.…”
Section: Introductionmentioning
confidence: 50%
See 1 more Smart Citation
“…Porokeratosis was found in younger women without any significant past medical history. Oral isotretinoin showed moderate improvement [73][74][75].…”
Section: Porokeratosismentioning
confidence: 97%
“…Compared with the other current combination or single treatments of lichen planus, acitretin is the first-line therapy for cutaneous lichen planus. Seven patients whose lesions were resistant to other treatments received isotretinoin for painful oral lichen planus as well as generalized pruritic lichen planus, and good to excellent results during the treatment, which never exceeded 2 months, were obtained [74]. Among all systemic retinoids, only acitretin has shown a relatively good level of evidence of its efficacy in the treatment of cutaneous lichen planus [166].…”
Section: Cutaneous Lichen Planusmentioning
confidence: 99%